Frequent exercise: A healthy habit or a behavioral addiction? - Wan-Jing Chen (KeAi Communications Co., Ltd., 2016)
It is well known that regular physical activity helps improve overall health and fitness and reduces the risk of many chronic diseases. However, excessive exercise might be harmful. Exercise addiction (EA) is a pattern of uncontrolled exercise that involves a craving for overwhelming exercise with addictive attributes. So far, little is known about this unique behavioral addiction. The aim of the current study is to introduce the diagnosis and assessment of EA, and to summarize several developing theoretical models. Eating disorders, body image disorder, low self-esteem, and high narcissism are related to high risk of EA. The paper also discusses the distinction between EA and highly involved physical activity. Keywords: Exercise addiction, Behavior addiction, Physical activity, Theoretical model